Rail infrastructure developments and their productivity impact with special reference to institutions in five Southern African development community countries - Dzawanda, Bernard (University of the Witwatersrand, Johannesburg, 2023)
This thesis investigates the determinants of rail infrastructure investment and its impact on productivity growth in Botswana, Namibia, South Africa, Zambia and Zimbabwe for the period 1960 to 2018. The descriptive analysis of rail infrastructure data covers the period from 1939 to 2018. With the exception of South Africa, data availability limited the study analytics to start from 1960. The five Southern African Development Community (SADC) countries share a common history in terms of development, and their rail networks are interconnected. The focus of the study is on the quantity of rail infrastructure. Based on the augmented Bond, Mairesse, and Mulkay (1997) investment model, we apply the Pooled Mean Group estimator of Pesaran, Shin and Smith (1999) on novel datasets of rail infrastructure measures to estimate the drivers of rail infrastructure investment and efficiency in Botswana, Namibia, Zambia and Zimbabwe. Estimation results suggest that economic, geostrategic and institutional factors drive rail infrastructure investment, efficiency and productivity growth in the four countries. GDP is found to have an insignificant impact on rail infrastructure investment. South Africa being distinctly different from the other four countries provides a different contextual setting to investigate the determinants of rail infrastructure investment and efficiency, and its impact on productivity growth. We separately apply time series analysis in the case of South Africa using the Bounds Test technique of Pesaran, Shin and Smith (2001). Estimation results suggest that GDP has a significant negative impact on rail infrastructure investment in South Africa. Government investment has a significant negative impact on rail infrastructure investment. Research results suggest that geostrategic factors have a significant positive impact on rail infrastructure investment in the four countries, and insignificant on rail infrastructure efficiency except in the case of passenger rail infrastructure investment where the impact is negative. In contrast, geostrategic factors have an insignificant impact on rail infrastructure investment in South Africa except for mixed rail infrastructure investment where the impact is negative. The impact of geostrategic factors on rail infrastructure efficiency in South Africa is found to be positive.
A thesis submitted in fulfillment of the requirements for the degree of Doctor of Philosophy Economics University of the Witwatersrand, Johannesburg, 2023
Keywords: Infrastructure investment; Productivity; Rail infastructure development; Community development; UCTD; SDG-12: Responsible consumption and production